Silicon Nanocrystals Synthesized from Silicon Tetrachloride Using Electron Beam Reduction Reaction#. (20th February 2015) - Lee, Don‐Sung; Kang, Hyun Suk; Koh, Ye‐Seul; Lee, Byung Cheol; Jeong, Hyun‐Dam
<x xml:space="preserve">Abstract</x> Si nanocrystals (NCs) were prepared by a new synthetic method using electron beam (e‐beam) reduction reaction (EBRR), obtaining crystals of the diamond cubic crystalline phase. New features in ultraviolet–visible (UV–vis) absorption and photoluminescence (PL) spectroscopies in the case of e‐beam‐irradiated samples were attributed to the formation of Si NCs and were confirmed by fast Fourier transform (FFT) processed images of thefrom field‐emission transmission electron microscopy (FE‐TEM) analysis. By the FFT processing, lattice fringes with d‐spacings of 2.19 and 1.99 Å were clearly observed, corresponding to the (211) and (220) planes of diamond cubic structured Si NCs. The possibility of the formation of the Si NCs was also validated by the Gibbs free energy calculations of the proposed reaction mechanism on EBRR of the SiCl4 precursor. In the calculation results, the Δ G values of the silicon cluster formation reaction were found to is decreased as the number of silicon atoms is increased, indicating that the silicon cluster formation reaction by the direct reaction of SiCl4 and the IPA radical is spontaneous. From the optical, theoretical, and high‐resolution HR‐TEM results, we confirmed the synthesis of Si NCs by EBRR. To the best of our knowledge, this is the first work to demonstrate the EBRR synthesis of Si NCs. This newly designed synthetic method is very promising for the large‐scale production of Si NCs for various applications. <boxed-text content-type="graphic" id="bkcs10188-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>